Epidemiology of substance use among secondary school learners in Atteridgeville, Gauteng - S V Moodley; M J Matjila; M Y H Moosa (South African Journal of Psychiatry, 2012)
Introduction. Adolescent substance use has a number of adverse consequences for both the individual and society. Anecdotal evidence suggested the existence of a serious substance use problem among learners in Atteridgeville, part of the City of Tshwane Metropolitan Municipality in Gauteng, South Africa. Objectives. The objectives of the study were to determine the prevalence rates and age of initiation of substance use among learners attending secondary schools in Atteridgeville, and the factors, if any, associated with cannabis use.